PENGEMBANGAN BAHAN AJAR ILMU PENGETAHUAN SOSIAL TERPADU DENGAN PENDEKATAN KONTEKSTUAL PADA SMP KELAS IX SEMESTER I - Budi Purnomo (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Learning of social science in yunior high school have several problem, include: not yet integrated learning of social science with laws of minister educations number 22 years 2006 because not integrated provide material study or learning of social science mainly carried out separate and not available text books that are contructed integrally.The research to do are developing materials study of integrated social scence with contexstual approach can be one solutions problem learning social science in yunior high school.Aims to developing material study of integrated social science with contexstual  approach are: 1) resulting of material study integrated social science that exciting and appropriate for yunior high school class IX  in the first semester. 2) developing of material study integrated social science that appropriate on yunior high school class IX in the first semester with contexstual approach.Done development with four stage include analysis, design development and evaluations. Evalution stage done with individual trials to three students. Result of trial draft to give the expert team consist of one person have skill social science and one person have skill design for validation.Product have been validated than tested to the students in small group, to know more useful product than to do field test.Result of testing product obtained quality as: (1) field study aspects obtained very good quality with 86,5% and average value 4,325, (2)  design aspect with category very good 90,04% and average value 4,52, (3) test small group include good category with 82,19% and average value 4,10, (4) field test obtained very good quality with 84,23% and 88,35%. Avarage value 4,21 and 4,42, so average value pretest 68,91 and 41,10, and average value postest 93,25 and 84,34.Base on result trial product can be conducted that product is very exciting/appropriate  as material study on yunior high scholl clas 1X in the first semester.These materials study (module) can be used student independently or with teacher guidance on learning social science in class.Key  words: material study of integrated social science, contexstual approach.